LOAD CURRENT DEPENDENT FUZZY LOGIC BASED CONTROLLER FOR BUCK DC/DC CONVERTER - Radhi, Jawad; Ali, Dr. Ramzi S.; Fathel, Dr. Ali (Iraqi Journal for Electrical and Electronic Engineering, 2006)
This paper presents and discusses a buck DC/DC converter control based on fuzzy logic approach, in which the fuzzy controller has been driven by voltage error signal and a current error signal for which the load current has been taken as a reference one. The validity of the proposed approach has been examined through starting the buck DC/DC converter at different loading and input voltages (to monitor the starting performances), exposing the converter into large load resistance and input voltage step variations (to explore its dynamic performance), in addition to step and smooth variation in the reference voltage (to see its ability in readjusting its operating point to comply with the new setting). The simulation results presented an excellent load & line regulations abilities in addition to a good reference tracking ability. It also showed the possibility of using the buck converter as smooth variable voltage source (under smooth reference voltage variations).